2019
DOI: 10.18632/aging.102522
|View full text |Cite
|
Sign up to set email alerts
|

Active compounds of herbs ameliorate impaired cognition in APP/PS1 mouse model of Alzheimer’s disease

Abstract: Alzheimer’s disease (AD), the most common cause of dementia, is a neurodegenerative disorder characterized by amyloid plaque accumulations, intracellular tangles and neuronal loss in certain brain regions. It has been shown that a disturbance of normal iron metabolism contributes to the pathophysiology of AD. However, the mechanism underlying abnormal iron load in the brain of AD patients is unclear. The frontal cortex, an important brain structure for executive function, is one of the regions affected by AD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…In particular, Aβ plaques found in the AD cortex and hippocampi are associated with iron deposits and ferritin [37][38][39]. In accordance with previous studies of AD model mice [40][41][42], we demonstrated significant increases of ferritin in the cortex of 7-month-old 5xFAD mice. Since ferritin is responsible for attenuation and sequestration of free iron [43], ADassociated increases of ferritin levels may indicate elevated labile iron level in the brain.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, Aβ plaques found in the AD cortex and hippocampi are associated with iron deposits and ferritin [37][38][39]. In accordance with previous studies of AD model mice [40][41][42], we demonstrated significant increases of ferritin in the cortex of 7-month-old 5xFAD mice. Since ferritin is responsible for attenuation and sequestration of free iron [43], ADassociated increases of ferritin levels may indicate elevated labile iron level in the brain.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, transferrin receptor protein 1 (Tfr1), the major vehicle of iron delivery into cells, also was significantly upregulated in AD mice. Treatment with the active compounds of herbs ameliorate impaired cognition and this beneficial effect is associated with reduced impairment of iron metabolism ( Yu et al, 2019 ; Ma et al, 2021 ). Thus, enhancing iron export or inhibiting iron transport could be a promising strategy to reduce the ferroptotic cell death in this disease.…”
Section: Ferroptosis-related Signaling Pathways In Admentioning
confidence: 99%
“…First, PUE can generate multiple beneficial effects by manipulation of different signal pathways, but we primarily focused on PI3K/Akt signal activation‐mediated suppression of the NF‐κB pathway. Hence, PUE may exert neuroprotective effects by other signal pathways such as the Nrf2 signaling pathway 32 and iron metabolism pathway 25 . Second, the collagenase‐induced rat ICH model itself cannot completely mirror the pathophysiological process of ICH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, PUE may exert neuroprotective effects by other signal pathways such as the Nrf2 signaling pathway 32 and iron metabolism pathway. 25 Second, the collagenase‐induced rat ICH model itself cannot completely mirror the pathophysiological process of ICH patients. Thus, results from our research might need to be further verified with other ICH models such as autologous blood and hemoglobin injection and be carefully explained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation